2010
DOI: 10.1002/jgm.1480
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of central nervous system α‐N‐acetylglucosaminidase activity and therapeutic benefits in mucopolysaccharidosis IIIB mice by a single intracisternal recombinant adeno‐associated viral type 2 vector delivery

Abstract: A single IC rAAV2 gene delivery is functionally beneficial for treating the CNS disease of MPS IIIB in mice. It is immediately clinically translatable, with the potential of improving the quality of life for patients with MPS IIIB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…Different AAV vector serotypes have been tested after intra-CSF delivery in LSD animal models with variable outcomes. In most cases, widespread CNS vector distribution was reported (19)(20)(21), with the exception of i.c.v. administration of AAV4 that resulted in the exclusive transduction of ependyma (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different AAV vector serotypes have been tested after intra-CSF delivery in LSD animal models with variable outcomes. In most cases, widespread CNS vector distribution was reported (19)(20)(21), with the exception of i.c.v. administration of AAV4 that resulted in the exclusive transduction of ependyma (52).…”
Section: Discussionmentioning
confidence: 99%
“…Adenoassociated virus (AAV) vector-mediated gene transfer, in particular, has shown promising results as an in vivo gene transfer tool, showing longterm production of therapeutic proteins in animal models and in humans (14)(15)(16). Extensive gene delivery to the CNS using AAV vectors has been achieved by multiple direct injections into the brain parenchyma (17,18) or by delivery to the cerebrospinal fluid (CSF) (19)(20)(21). Direct delivery of AAV vectors to the brain parenchyma is being clinically explored in MPS IIIA.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies on gene therapy for MPS III have mainly focused on the correction of the neurodegeneration. As shown in Table 1, AAV [66,70-75], lentivirus [70,76-78] and canine adenovirus (AdV) vectors [79,80] have been evaluated for MPS IIIA and IIIB gene therapies, which have been delivered intravenously or by direct brain injection (i.e., intracranial, intraventricular, intracisternal or intracranial). A common approach for the treatment of MPS III was intravenous pretreatment with mannitol, which in most cases allowed an increase of the number of transduced cells in both brain and peripheral organs, as well as improvement of the therapeutic effect of the therapy [71,72,75,78].…”
Section: Advanced Therapies For Morquio a Syndromementioning
confidence: 99%
“…As shown in Table 1, AAV [66,70-75], lentivirus [70,76-78] and canine adenovirus (AdV) vectors [79,80] have been evaluated for MPS IIIA and IIIB gene therapies, which have been delivered intravenously or by direct brain injection (i.e., intracranial, intraventricular, intracisternal or intracranial). A common approach for the treatment of MPS III was intravenous pretreatment with mannitol, which in most cases allowed an increase of the number of transduced cells in both brain and peripheral organs, as well as improvement of the therapeutic effect of the therapy [71,72,75,78]. Except for the studies carried out with canine AdV vector [79,80], gene therapy for MPS IIIA and IIIB showed long-term vector maintenance and expression, improvement in behavioral performance, reduction of GAG in urine and/or tissues, increase in life span and normalization of secondary enzymatic activities (e.g., β-glucuronidase or β-hexosaminidase).…”
Section: Advanced Therapies For Morquio a Syndromementioning
confidence: 99%
“…More recently, a widespread enzymatic correction of CNS tissues was obtained after one single intracerebral injection of therapeutic lentiviral vector in leukodystrophy mouse models (Lattanzi et al, 2010). Several other teams have shown promising results in MPS IIIB, MPS I, MPS IIIA mouse or dog models, using either intracranial AAV-mediated gene therapy (Heldermon et al, 2010;Ellinwood et al, 2011;McIntyre et al, 2010;Fraldi et al, 2007) or intracisternal AAV gene transfer (Fu et al, 2010).…”
Section: In Vivo Gene Therapymentioning
confidence: 99%